The effects of HIIT in the heat with permissive dehydration will elicit thermoregulatory and cardiovascular adaptations in Paralympic athletes. - Malcolm, k. R. (Journal of Australian Strength and Conditioning, 2019)
High Intensity Interval Training in the heat is a simple means to elicit beneficial thermoregulatory and cardiovascular adaptations in Paralympic athletes. Such training should be used two-three weeks prior to competition in hot and humid environments.